MODIFIKASI MEDIA ALTERNATIF DARI SAYURAN UNTUK ANALISIS KUANTITATIF PERTUMBUHAN MIKROORGANISME ASAL TANAH GAMBUT KALIMANTAN BARAT DENGAN METODE TPC - Rezekikasari Rezekikasari; Rudi Harianto (Fakultas Pertanian Universitas Tanjungpura, 2019)
Medium formulations for quantitative testing and isolation of microorganism from peat soils, require adequate nutrition. This needs to be supported by the type of substrate and incubation conditions that support each other. Isolation media used mostly though available, but the price is quite high. This is what underlies the need to find alternative sources of new substrates that can support the growth of microbes from peat soils. Some of these ingredients include, carrots, Gembili Bulbs, tomatoes, and pumpkin which are abundantly available in West Kalimantan. This study shows that the best substrate in isolation of bacteria and fungi from peat is Gembili Bulbs with a total colony of 26 x 105 (CFU / gr) and fungi of 10 x 105 (CFU / gr). Peat bacteria and fungus cannot grow on carrot and pumpkin substrate media as indicated by the absence of growing microbial colonies. The best formulation of microbial isolation media with Gembili Bulbs is also supported by the highest C / N ratio of 44.8.Key Words : Bacteria, Fungi, Quantitative, Pour Plate Methode, TPC